2018
DOI: 10.1016/j.jash.2018.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone, inactive matrix gla-protein, and large artery stiffness in hypertension

Abstract: Vascular calcification leads to increased large artery stiffness. Matrix gla-protein (MGP) is a vitamin K-dependent protein that inhibits arterial calcification. Aldosterone promotes vascular calcification and stiffness, but the relationships between aldosterone, MGP, and arterial stiffness are unknown. We studied 199 adults (predominantly older men) with hypertension. We assessed the relationship between levels of dephospho-uncarboxylated MGP (dp-ucMGP), aldosterone, and carotid-femoral pulse wave velocity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…9 For this reason, previous studies have suggested that MGP influences vascular stiffness through its role in preventing calcification. 20,57 It was interesting, therefore, that ucMGP levels were associated with vascular stiffness in the absence of an association with detectable vascular calcification. However, our study is limited in that the human and mouse imaging techniques may not be able to detect microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
“…9 For this reason, previous studies have suggested that MGP influences vascular stiffness through its role in preventing calcification. 20,57 It was interesting, therefore, that ucMGP levels were associated with vascular stiffness in the absence of an association with detectable vascular calcification. However, our study is limited in that the human and mouse imaging techniques may not be able to detect microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
“…69 In this regard, aldosterone is associated with high levels of inactive matrix Gla protein, a vitamin K-dependent protein that inhibits arterial calcification. 70 Spironolactone could also reduce aortic stiffness in stage 3 CKD through the reduction of vascular fibrosis. 71 However, its use in more advanced stages of CKD should be carefully evaluated because of the risk of hyperkalaemia.…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Vitamin K status in co-morbidities associated with poor Coronavirus disease 2019 outcomes dp-ucMGP levels are elevated in various diseases that are associated with elastic fibre calcification and degradation such as diabetes (35) , hypertension (36) , CVD (37) , chronic kidney disease (35,38) and obesity (39) . It is possible that reduced vitamin K intake increases the risk of developing these conditions (40) .…”
Section: Vitamin K Metabolism In Coronavirus Disease 2019mentioning
confidence: 99%